2003
DOI: 10.1159/000068066
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of Supraventricular Tachycardia Exhibiting Hydrops fetalis with Flecainide Acetate

Abstract: Background: The efficacy of flecainide acetate for the treatment of fetal supraventricular tachycardia with hydrops fetalis and changes in venous blood flow patterns in the fetus during treatment are reported. Case: Oral flecainide administration was started at 30 weeks of gestation. Cardioversion was achieved 6 days after treatment. Sustained abnormal venous Doppler indices were shown and complete normalization of venous returns was observed 6 days after cardioversion. A vigorous male baby was born, and he is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…One of the potential adverse effects with sotalol is the possible proarrhythmic effects in both the mother and the fetus [7] . Flecainide has been used successfully in a number of case series to treat hydropic and nonhydropic fetuses with SVT; however, there have been concerns about fatal proarrhythmic effects and fetal death in utero with this medication [7,13] . The choice of antiarrhythmic agents is also limited if there is liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…One of the potential adverse effects with sotalol is the possible proarrhythmic effects in both the mother and the fetus [7] . Flecainide has been used successfully in a number of case series to treat hydropic and nonhydropic fetuses with SVT; however, there have been concerns about fatal proarrhythmic effects and fetal death in utero with this medication [7,13] . The choice of antiarrhythmic agents is also limited if there is liver disease.…”
Section: Discussionmentioning
confidence: 99%
“…However, several investigators have indicated some therapeutic methods. In cases of hydrops fetalis caused by SVT, elevated preload condition was reported 7 and successful transplacental therapy has been reported 8 . Pericardiocentesis is indicated for cardiac decompression in fetuses with pericardial effusion in cases with teratoma 9 .…”
Section: Discussionmentioning
confidence: 99%
“…In fetal life, the most common cardiac tumor is rhabdomyoma [35]. In contrast, fibroma, teratoma and hemangioma are less frequent [35].…”
Section: Cardiac/pericardial Tumorsmentioning
confidence: 99%